What successful teachers do in inclusive classrooms : 60 research-based teaching strategies that help special learners succeed - McNary, Sarah J.; Glasgow, Neal A.; Hicks, Cathy D. (Thousand Oaks, Calif : Corwin Press, 2005)
Bridging the gap between theory and practice, this book focuses on extending academic research to classroom practices that address the problems faced by teachers working with special needs students in inclusive classrooms. It includes 60 research-based strategies that give teachers the tools and confidence to engage their special needs learners. It deciphers the latest research and makes it accessible and applicable for day-to-day classroom practice.
Includes bibliographical references and index.
Keywords: Inclusive education; Effective teaching; Classroom management